Patients acceptance and comprehension to written and verbal consent (PAC–VC) - Rabia Kashur; Justin Ezekowitz; Shane Kimber; Robert C. Welsh (BMC Medical Ethics, 2023)
Abstract Background Acute myocardial infarction (AMI) research is challenging as it requires enrollment of acutely ill patients. Patients are generally in a suboptimal state for providing informed consent. Patients’ understanding to verbal assents have not been previously examined in AMI research. Patients Acceptance and Comprehension to Written and Verbal Consent (PAC–VC) compared patients’ understanding and attitudes to verbal and written consents in AMI RCTs. Methods PAC–VC recruited patients from 3 AMI trials using both verbal N = 12 and written N = 6 consents. We compared patients’ understanding using two survey questionnaires. The first questionnaire used open-ended questions with multiple choice answers. The second questionnaire used a 5-point Likert scale to measure patients understanding and attitudes to the consent process. Overall answers average scores were categorized into three groups: Adequate understanding (71–100) %, Partial understanding (41–70)% and Inadequate understanding (0–40)%. Results Responses showed patients with verbal assent had adequate understanding to most components of informed consent, close to those of written consent. Most patients did not read written information entirely and believed that it is not important to make a final decision. Patients favoured to have written information be part of the consent but not necessarily presented during the initial consent process. Patients felt less pressured in the verbal assent arm than those of written consent. Conclusion Patients had adequate understanding to most components of verbal assent and comparable to those of written consent. Utilizing verbal assents in the acute care setting should be further assessed in larger trials.